Pembatalan Tiket Jasa Transportasi Kereta Api dan Perubahan Jadwal Penumpang Perspektif Hukum Ekonomi Syari’ah - Fawaid Fawaid (Program Pascasarjana Universitas Ibrahimy, 2020)
In conducting research, the authors use Islamic economic law research methods that adopt qualitative research methods including both primary data sources and secondary data, data collection techniques namely observation, interviews, documentation, data analysis techniques namely editing and organizing, checking the validity of data, and stages research stage. All this researchers use to find research results. The findings in this study are as follows: 1. In running a business as a transportation service provider, PT Kereta Api does not only focus on sales but also serves to cancel and change the schedules. 2. There are two kinds of cancellations, namely canceled buyers and canceled officers. 3. Cancellations and schedule changes are both manual and online. 4. Cancellation and schedule changes can be made as long as not exceeding the specified time limit. 5. In canceling and changing passengers' schedules, an administration fee of 25% of the ticket price is subject to administration.